Gogreen App: Mobile application development for ethical waste management / Aimi Syahrul Che Aziz - Che Aziz, Aimi Syahrul (2021)
Waste management is not an alien issue to the current world. Waste generators adopt poor solid waste management practices due to a lack of awareness of them. The goal of this project is for GoGreen App - Mobile Application Development for Ethical Waste Management to be able to give customers a contemporary, pleasant platform that allows them to experience a better recycling process. The objectives of this project is to identify the user requirements, design and develop the GoGreen App - Mobile Application for Ethical Waste Management using the Android Studio platform and Mobile Application Development Life Cycle (MADLC) up until the testing phase. Nowadays, environmental issues have become one of the priorities for local authorities that need thousands of ringgits for gathering and disposing of trash or waste activities. Despite the fact that government rules are expanding the number of recycling activities, most recycling is still driven by economic market forces and volunteer initiatives. It is said that through raising consumer awareness of waste management, and encouraging them to manage their trash disposal rather than storing it or disposing of it in an uncontrolled manner. Therefore, the existing effort needs to be improved so not only the awareness of recycling culture can rise, but also the right knowledge of how to imply it, mainly among school and university students, as the saying goes: strike while the iron is hot. Therefore, this project is intended to create a recycling educational-related mobile application that will help educate people about the proper way to manage their waste.